ANALISIS PENDIDIKAN KARAKTER DALAM LITERASI BUDAYA DAN KEWARGAAN MELALUI KEGIATAN EKSTRAKURIKULER TARI DI SD SUPRIYADI SEMARANG - Nofiyanti, Afroh; Agustini, Ferina; Setyaningsi, Ariani Nur (STKIP Persada Khatulistiwa Sintang, 2024)
This study aims to analyze extracurricular dance activities towards character education, cultural literacy, and citizenship at SD Supriyadi Semarang. Through interviews with teachers, students, and parents, as well as observations of dance activities, this study found that dance activities significantly contribute to the formation of students' character, such as discipline, cooperation, and self-confidence. Dance activities also serve as an effective media to improve cultural literacy by introducing students to traditional dances and the meaning of local culture. In addition, dance performances at various school and community events strengthen students' sense of citizenship and social responsibility. These findings indicate that extracurricular dance not only develops artistic skills but also provides benefits in aspects of character education, culture, and citizenship of students. This study recommends strengthening extracurricular arts activities as an integral part of the curriculum to support students' holistic development.